Anatomia foliar e trocas gasosas de Prunus myrtifolia (L.) Urb em diferentes altitudes na Serra da Mantiqueira-MG - Freitas, Bethânia Silva Morais de (2017)
Environmental changes from montane forest can provide great opportunities to explain the responses physiological and morphological of the plant found in high-altitude environments. The species Prunus myrtifolia of the family Rosaceae is a species that stands out for its occurrence characteristic of Atlantic Forest. The objective of this work was to analyze the gas exchange and leaf anatomy of Prunus myrtifolia in four altitude levels (1500, 1700, 1900 and 2100 m altitude) of an Montane Cloud Forest in Itamonte-MG. For the characteristics of gas exchanges, was used the infrared gas exchange analyzer and were analyzed 6 leaves of 3 individuals/altitude level. For an anatomy, leaves were collected and were made by printing the abaxial surface and as cross-sections through embedding in historesin, obtained with the aid of a rotating micrometer. Physiological variables such as photosynthesis, stomatal conductance, internal carbon, transpiration and Ci / Ca ratio were higher in the altitude of 2100 m. The thickness palisade parenchyma and a mesophyll increased with an elevation of the altitude and the stomatal density was less than 2100 m and greater than 1500 m. The results obtained showed that in Prunus myrtifolia the increase in the thickness of the tissues and the better diffusion of the CO2, through the greater stomatal opening, are relevant characters in the adaptation of the species to 2100 m of altitude.